Developing an obstetric care screening tool to improve social support access for pregnant women: A prospective cohort study - Kawaguchi, Haruna; Shinohara, Ryoji; Akiyama, Yuka; Kushima, Megumi; Matsuda, Yoshio; Yoneyama, Marie; Yamamoto, Tomomi; Yamagata, Zentaro (Frontiers in Global Women's Health, 2023)
Background This study aimed to develop an efficient interview sheet during pregnancy and screening tool to identify pregnant women needing social support at obstetric institutions. Moreover, we investigate the perinatal factors associated with the Edinburgh postnatal depression scale (EPDS). Methods This prospective cohort study was conducted at three medical institutions that commonly encounter cases with social issues. Pregnant women were assessed using an interview sheet at the first visit (n = 678), at approximately 28 weeks gestation (n = 495), 36 weeks gestation (n = 296), and the postpartum period (n = 822). We investigated the important items identified on the new screening questionnaire (NEW interview sheets) for women needing social support. The items on the interview sheet were scored by multiple linear regression analysis, and the cutoff values were calculated using the receiver operating characteristic curve. The association between perinatal factors and EPDS was assessed using multiple logistic regression analyses. Results The study included 166 cases for which all NEW interview sheets for all periods were available. NEW interview sheets and stepwise screening tools during the first and second trimester were developed in which 2.5% of pregnant women were identified as requiring social support, respectively. The factors associated with EPDS ≧ 9 were “Women who felt confused/troubled or did not feel anything to be pregnant” (adjusted odds ratio [aOR]: 6.51, 95% conﬁdence interval [CI]: 1.62–26.15), “Maternal mental disorder” (aOR 4.38; CI 1.06–18.10), “Consultation request at first visit” (aOR 3.22; CI 1.09–9.45), and “Women who have difficulty or anxiety about pregnancy during the second trimester” (aOR 3.14; CI 1.29–7.67). Conclusions We created the NEW interview sheets and screening tools during the first and the second trimester. Future studies are needed to validate these screening tools.